Economic Institutions, Technological Innovation, and Social Capital for the Welfare of Fishermen in Kedonganan Village, Badung Regency, Bali Province (International Journal of Educational Technology Research, 2024)
Improving the welfare of fishermen requires changes and innovations in the institutional components of fishermen, technological innovation where technology has the aim of maintaining ecological balance so that it can be maximally useful today, and in the economic dimension, technology plays an important role, especially for the creation of efficient production, as well as increasing competitiveness and added value in increasing fishermen's business profits. The location of the study was conducted in Kedonganan Village, Badung Regency, Bali Province, which is a coastal area and mostly makes a living as fishermen. This type of research is qualitative research with data analysis methods using existing theories to solve problems in research. This research uses data analysis techniques, namely qualitative data analysis. The results showed that  (1) The institutions of fishermen groups in Kedonganan Village play an active and compact role, as well as good communication and cooperation between members of fishermen groups in Kedonganan Village. (2) Institutional strengthening models to improve the welfare of fishing communities in Kedonganan Village